2017
DOI: 10.1038/s41467-017-00129-y
|View full text |Cite
|
Sign up to set email alerts
|

ROCKII inhibition promotes the maturation of human pancreatic beta-like cells

Abstract: Diabetes is linked to loss of pancreatic beta-cells. Pluripotent stem cells offer a valuable source of human beta-cells for basic studies of their biology and translational applications. However, the signalling pathways that regulate beta-cell development and functional maturation are not fully understood. Here we report a high content chemical screen, revealing that H1152, a ROCK inhibitor, promotes the robust generation of insulin-expressing cells from multiple hPSC lines. The insulin expressing cells obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 34 publications
0
65
0
1
Order By: Relevance
“…Although current protocols produce human b-like cells with some functionality (Pagliuca et al, 2014;Rezania et al, 2014;Russ et al, 2015), the differentiation efficiency varies greatly among different hPSC lines. For instance, most studies utilize HUES8 (Pagliuca et al, 2014;Veres et al, 2019) or H1 (Ghazizadeh et al, 2017;Rezania et al, 2014) hESCs, which have been shown to be efficient in b cell lineage commitment. The same protocol, when applied to other cell lines, including patient-specific iPSCs, could result in poor b cell specification (Ghazizadeh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although current protocols produce human b-like cells with some functionality (Pagliuca et al, 2014;Rezania et al, 2014;Russ et al, 2015), the differentiation efficiency varies greatly among different hPSC lines. For instance, most studies utilize HUES8 (Pagliuca et al, 2014;Veres et al, 2019) or H1 (Ghazizadeh et al, 2017;Rezania et al, 2014) hESCs, which have been shown to be efficient in b cell lineage commitment. The same protocol, when applied to other cell lines, including patient-specific iPSCs, could result in poor b cell specification (Ghazizadeh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Modifications of these stepwise pathways facilitate the generation of neurogenin 3 (NGN3 + ) and/or neurogenic differentiation factor 1 (NEUROD1 + ) endocrine progenitor cells (Rezania et al, 2014), as well as monohormonal endocrine cells, including insulin-expressing b-like cells that are glucose responsive in vitro (Pagliuca et al, 2014;Rezania et al, 2014). More recently, Rho-associated coiled-coil containing protein kinase 2 (ROCKII) inhibition has also been found to promote the maturation of hPSC-derived b-like cells (Ghazizadeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…diMF has been extensively studied as a ROCK inhibitor and characterized in pre-clinical models. It promotes generation of pancreatic beta-like cells from human pluripotent stem cells [30], augments neurite extension [31], enhances proliferation and migration of endothelial progenitor cells [32], and triggers cell-cycle arrest and cellular senescence of mouse embryo fibroblasts [33]. However, ROCKindependent activity has also been ascribed to diMF.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports by us and others have detailed approaches for making insulin-producing β-like cells from human embryonic stem cells (hESCs) with the goal that these cells could be used for both cell replacement therapy and drug screening for diabetes [3][4][5][6][7][8]. These hESC-derived β (SC-β) cells are capable of undergoing glucose-stimulated insulin secretion and express markers found in β cells.…”
Section: Introductionmentioning
confidence: 99%